Response growth and yield of local black rice variety mutiara to drought stress - Purwanto Edi; Taqiy Apta Danendra Faiq; Cahyo Handoyo Gani; Rahayu Muji (BIO Web of Conferences)
Plant tolerance under drought stress has mechanisms to adapt to adverse impacts such as synthesizing proline compounds, increasing root length, changing physiological processes, inhibiting growth, and reducing yield of paddy. The purpose of this study was to determine the level of tolerance of local black rice variety mutiara in response to growth and yield to drought stress. The research used was a factorial Randomized Complete Block Design (RCBD) with two factors and 4 block. The first factor was watering interval (every 3 and 6 day). The second factor was soil moisture (100, 80, 60, and 40% Field Capacity/FC). The variables observed were longest roots, total grain weight, grain yield, chlorophyll content, transpiration rate and proline content. The results showed that 6 day watering interval can reduce total grain weight, grain yield, and increase longest roots and proline content compared to the 3-day watering interval. Soil moisture at FC up to 40% can reduce total grain weight, grain yield, chlorophyll content, and transpiration rate from 100% FC.